From the Arctic Ocean to Cannes : Women as Film Directors in Finland before 1962 - savolainen, tarja (2009)
Only abstract. Paper copies of master’s theses are listed in the Helka database (http://www.helsinki.fi/helka). Electronic copies of master’s theses are either available as open access or only on thesis terminals in the Helsinki University Library. Vain tiivistelmä. Sidottujen gradujen saatavuuden voit tarkistaa Helka-tietokannasta (http://www.helsinki.fi/helka). Digitaaliset gradut voivat olla luettavissa avoimesti verkossa tai rajoitetusti kirjaston opinnäytekioskeilla. Endast sammandrag. Inbundna avhandlingar kan sökas i Helka-databasen (http://www.helsinki.fi/helka). Elektroniska kopior av avhandlingar finns antingen öppet på nätet eller endast tillgängliga i bibliotekets avhandlingsterminaler. The subject of the study was Finnish women as film directors before 1962. Women's relation to film-making was approached as a negotiation between the director and film production. The analysis focused on questions involving the general events in society and especially in film production, as well as how women got their chances to direct films and what kind of meanings did women give to these opportunities. The study also explored how their personal resources, i.e. economic, cultural and social capitals, influenced their possibilities for attaining their positions in film production. The research shows that women were already interested and involved in film in many ways during the era of silent film. However, women did not direct before the 1930s and only three women directed a full length feature film. Ten film-makers of short films were found, but only three of them made several short films shown in the theatres. Seven women made 16 millimetre films and only a few 8 millimetre films. The chance for all three feature film directors to direct came suddenly, during a film production boom, when there was a lack of film directors. Regardless of how they became directors, they used their opportunities actively for different purposes. Eva-Lisa Viljanen and Brita Wrede represented film-makers of short films in the ...